Substituição isolada da valva aórtica em pacientes com função ventricular deprimida Aortic valve replacement in patients with depressed left ventricular ejection fraction - Gilberto Venossi Barbosa (Brazilian Journal of Cardiovascular Surgery, 1989)
Para avaliar o valor prognóstico da fração de ejeção do ventrículo esquerdo, entre 210 pacientes com lesões da valva aórtica operados, consecutivamente, entre maio de 1981 e outubro de 1988 e que receberam as próteses Omniscience e Meditronic-Hall, foram selecionados 112 e divididos, de acordo com a fração de ejeção do ventrículo esquerdo, em dois grupos: o G1 = FE > 40%, ficou com 52 pacientes com médias de idade 39 ± 12 anos, FE = 58 ± 10% e classe funcional (NYHA) = 2,8; o GE = FE < 40% ficou com 60 pacientes com médias de idade 48 ± 17 anos, FE = 27 ± 13% e (NYHA) = 3,6. Nas cirurgias, foram utilizados hipotermia e hemodiluição moderadas, oxigenador de bolhas, infusão cardioplégica St. Thomas. As médias dos tempos de circulação extracorpórea e parada cardíaca foram: no G1 =8 2 ± 18 e 49 ±7 minutos, e 96 ± 11 e 55 ± 6 minutos, no Grupo 2; o tamanho das próteses foi 25,2 ± 1,8 milímetros. No Grupo 1, a mortalidade imediata foi 3,8% no G1 e 5,8 no G2, e a tardia 4% no G1, e no G2 foi 8,7%. No G1 houve significante associação entre a mortalidade e a função ventricular sistólica. Clínicamente, no G1, 65% dos pacientes estão na (NYHA) I, 28% na II, 5% na III e 2% na IV. No G2, 46% estão na (NYHA) I, 25% na II, 13% na III, e 16% na IV. A sobrevida atuarial em sete anos foi 88 ± 2% no G1 e 76 ± 4% no G2. Portanto, os pacientes com FE < 40% apresentaram mortalidade mais elevada, menor sobrevida a curto e longo prazo e resultados clínicos menos satisfatórios. Para obtermos melhores resultados, devemos operar antes que a FE em repouso e exercício se torne deprimida, ou que apareça intolerância ao exercício moderado. To evaluate the prognostic value of resting left ventricular ejection fraction (LVEF) a series of 210 consecutive patients with aortic valve disease operated upon between May 1981 and October 1988 was studied retrospectively. All patients had their aortic valve replaced by Omniscience or Meditronic prosthesis; 112 formed the study group because they have complete follow up and cineangiocardiographic data. Based on pre-operatory left ventricular ejection fraction the patients were divided in two groups: Group 1 = 52 patients with LVEF > 40%, 39 ± 12 years, NYHA functional class 2.8, and EF 58 ± 10%. Group 2 = 60 patients with LVEF < 40, 48 ± 17 years, NYHA functional class 3.6, and LVEF of 27 ± 12%. During surgery moderate hypothermia and hemodilution were utilized, with dubble oxygenator and cardioplegia With St. Thomas cardioplegic solution. Mean extracorporeal circulation and cardiac arrest time were respectively 82 ± 18 and 49 ± 7 minutes in Group 1 and 96 ± 11 and 55 ± 6 minutes in Group 2. The size of the prosthesis were 25.2 ± 1.8 mm in Group 1. The short term mortality was 3.8% in Group 1 and 5.8 in Group 2. The long-term mortality was 4.0% in Group 1 and 8.7% in Group 2. In Group 1 there was a significant association between mortality and left ventricular systolic function. In the follow-up evaluation, among patients in Group 1, 65% were in class I, 28% were in functional class II, 5% in class III, and 2% in class IV. Among patients in group II 46% were in class I, 25% in class II, 13% in class III, and 16% in class IV. The 7 year survival rate was 88 ± 2% in Group 1 and 76 ± 4% in Group 2. Thus, patients with LVEF less than 40% had higher short and longterm mortality and worse clinical course. For better surgical results patients with aortic valve disease should be operated upon before the reduction of left ventricular systolic function.